Kenaikan Tingkat Kebisingan Ruangan Kelas Akibat Pengaruh Penyejuk Udara dan Lalu Lintas - I Made Indradjaja M. Brunner; Susy F. Rostiyanti (Fakultas Teknik, 2020)
Noise level in the classroom is a factor affecting the learning process. This study aims to determine the level of indoor noise of a private university campus in West Jakarta. Measurements were made using Sound Level Meter that can record the noise level every second with accuracy up to 0.1 dBA. Sampling was carried out in a number of classrooms in an empty condition, closed door, and air conditioning system either in off or on position. Classrooms are distinguished based on the condition of the wall, namely the window facing the outside environment and massive walls without windows to the environment. The measurement results indicate a significant difference in noise level at a 95% confidence level in an empty classroom when the air conditioning system is not functioning and when the system is running. Differences also occur in classrooms with and without windows to the environment. The difference shows that the classroom in an empty condition can experience an increase in latent noise level due to the operation of the air conditioner between 5.78-16.49 dBA. Increased noise from the environment including the highway is about 3 dBA for classrooms located on the 5th floor, with a horizontal distance about 100 meters from the highway and has thick and permanent glass windows.